Women Emancipation in the Romanian Society and Violence in the Family: Theoretical Aspects and Socio-Historical View - Bonea, Georgiana Virginia (Calitatea Vieții, 2018)
The main objective of this paper is to highlight and analyze the issue of violence against women within the family, in various historical and social contexts. Thus, the “basic cell of society”, as it is called the family, is analyzed from the perspective of the process of modernizing society and emancipating women. These are multiple family changes in gender mainstreaming, as well as mentalities about the role of women and men in family privacy. From a sociohistorical perspective, domestic violence has been a fact since ancient times, but postmodernity has led to the construction of specialized services to prevent and combat it. The Romanian society has gone a long way from the monarchy, to communism, post-communism and transition, a fact reflected with certainty in the various institutions of the state, as well as in the revolution of individual perspectives.